Projeto de sinalização para o ambiente da Faculdade de Tecnologia da UFAM - Reis, Kaylane Stefany Lelo dos (Brasil, 2025)
Signage is essential for providing information about the space and guiding the movement of users, ensuring that they find their destination quickly and independently. It functions as a form of social communication between the environment and people, promoting clarity about the space and its flows. When the user cannot understand the signage, the system becomes flawed. This project aims to develop a new signage system for the Faculty of Technology, based on methodologies inspired by Bruno Munari, Duailibi & Simonsen and the Valéria London Design office. The need arose due to the lack of adequate directional signage and the outdated nature of the existing elements. To this end, detailed analyses were carried out, which identified the main flaws of the current system, considering ergonomic and functional aspects. Based on these analyses, a new signage system was designed, more efficient and accessible, suited to the needs of the institution.